2009
DOI: 10.1080/01431160802427905
|View full text |Cite
|
Sign up to set email alerts
|

Correlated change in normalized difference vegetation index and the seasonal trajectory of photosynthetic capacity in a conifer stand

Abstract: Seasonal changes in canopy photosynthetic activity play an important role in carbon assimilation. However, few simulation models for estimating carbon balances have included them due to scarcity in quality data. This paper investigates some important aspects of the relationship between the seasonal trajectory of photosynthetic capacity and the time series of a common vegetation index (normalized difference vegetation index, NDVI), which was derived from on site micrometeorological measurements or smoothed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Studies by Wang et al (2008aWang et al ( , 2009) and Jin et al (2012) revealed noticeable inconsistencies in the relationship between V cmax and VIs in certain periods, for example, V cmax increasing with increasing VIs in spring and then decreasing or remaining steady with further increase of VIs. Stronger relationships might be obtained by allowing for hysteresis or asymmetric V cmax ÁVI relationships.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Studies by Wang et al (2008aWang et al ( , 2009) and Jin et al (2012) revealed noticeable inconsistencies in the relationship between V cmax and VIs in certain periods, for example, V cmax increasing with increasing VIs in spring and then decreasing or remaining steady with further increase of VIs. Stronger relationships might be obtained by allowing for hysteresis or asymmetric V cmax ÁVI relationships.…”
Section: Introductionmentioning
confidence: 93%
“…Research has shown that remotely sensed reflectance can provide a useful data source to sense photosynthetic capacity because of the linkage of reflectance with canopy photosynthesis (Gamon et al, 1995;Carter, 1998;Choudhury, 2001;Dobrowski et al, 2005). A variety of vegetation indices have been used that can be related to photosynthetic capacity, notably the normalised difference vegetation index (NDVI), and the enhanced vegetation index (EVI) (Wang et al, 2009;Jin et al, 2012;Muraoka et al, 2012;Houborg et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Scenario 2 performs best. This is because the broadband NDVI has a closer relationship with canopy physiology than its remote sensing counterparts (Wang et al 2009). Even so, the satellite-borne NDVI time-series can still provide useful information on the seasonality of canopy physiology and improve the daily model performance, as indicted in table 1.…”
Section: Performance Of the Models In Gpp Simulationmentioning
confidence: 97%
“…Since the analysis in Wang et al (2009) was based on relative daily average V rm , the parameter a 1 was obtained by multiplying parameter a in Wang et al (2009) with species-specific V m,25 , while parameter b 1 was kept the same as b in Wang et al (2009). Therefore, seasonal changes in canopy physiology were retrieved for the first time in this paper from commonly available NDVI time-series.…”
Section: A~1mentioning
confidence: 99%
See 1 more Smart Citation